Antimicrobial and production of hydrolytic enzymes potentials of bacteria and fungi associated with macroalgae and their applications: a review - Vega-Portalatino, Edwin Jorge; Rosales-Cuentas, Miriam Marleni; Valdiviezo-Marcelo, Jaime; Arana-Torres, Nancy Maribel; Espinoza-Espinoza, Luis Alfredo; Moreno-Quispe, Luz Arelis; Cornelio-Santiago, Heber Peleg (Frontiers in Marine Science, 2023)
Endophytic and epiphytic bacteria and fungi that live in association with macroalgae produce compounds that favor the growth of the host, being in some cases more efficient than those produced by the terrestrial microbiome. This review collects information from articles published in Scopus, ScienceDirect, PubMed, Wiley Online Library and they were organized according to their antimicrobial properties, synthesis of hydrolytic enzymes, production of other bioactive compounds by bacteria and fungi, and their application. The information collected showed that bacteria and fungi associated with macroalgae have the ability to inhibit bacteria, fungi, yeasts, and protozoa that affect aquaculture, public health, and the food industry, reporting that the pyrenocines A, B, E and S isolated from Phaeosphaeria sp. inhibited pathogenic protozoa. Additionally, other compounds identified as alkaloids, steroids, triterpenoids and flavonoids could act by altering the morphology and physiology of pathogenic microorganisms, which can be applied in the food, pharmaceutical, paper, chemical, textile and cosmetic industries. In addition, these microorganisms can synthesize enzymes such as xylanase, amylase, cellulase, pectinase, agarase, lignocellulose, chitinase, gelatinase, asparaginase, glutaminase and lipase, which can be used to reduce oxidation and enzymatic browning, improve digestibility and functionality of feed, synthesis of chitin oligomers with antimicrobial properties, bioremediation of agricultural residues, industrial effluents and production of hydrolysates.